Some approaches in policy study - Dinh, Dang Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The article, after providing definitions of policy, public policy and analyzing main contents of policy study, turns attention on the two main topics: i) Analysis of some focused approaches for policy study, and ii) Proposal of some recommendations for policy setting in Vietnam. For the first topic, recommendations are made for approaches such as: recognition of paradox of the role of policy setting and impacts from policies among social groups, identification of standard conformity of policies, proposal of strategies to secure the right course of policies, recovery of “system faults”, analysis of consequences of policies to issue solutions to recover at highest level negative impacts from policies. In connection to Vietnam reality, on basis of point by Prof. Kenichi Ohno, Japanese Institute of Economic Studies: “The system of policies of Vietnam, up to now, does not really give the important contribution for the country’s development”, the author notes the necessity of an innovative model in policy setting in Vietnam which would attract participation of social layers, particularly business community, social organizations and large public communities where the “technocrat” group of excellent individuals has to have an adequate role. Code: 13091801 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">